Racial justice and the limits of law - Malkani, Bharat (Bristol University Press, 2024)
Racial justice is never far from the headlines. The Windrush scandal, the toppling of the statue of Edward Colston, and racism within the police have all recently captured the public's attention and generated legal action. But, although the ideals of the legal system such as fairness and equality seem allied to the struggle for racial justice, all too often campaigners have been let down by the system. This book examines law's troubled relationship with racial justice. It explains that law's historical role in creating and perpetuating racial injustices continues to stifle its ability to advance the cause of racial justice today. Both a lawyer's guide to antiracism, and an antiracist's guide to legal action, it unites these perspectives to help both groups understand how to use the law to tackle racial injustices